Determination of factors influencing pre-service teachers’ sense of self-efficacy - Ngidi, D.P.; Ngidi, S.A. (South African Journal of Higher Education, 2019)
This study examined the factors that influence the sense of self efficacy of pre-service teachers at a university of technology in South Africa. To this end, a questionnaire was used in a survey to collect data from the population of fourth-year Bachelor of Education students. The Teachers’ Sense of Efficacy Scale (TSES) was used to measure the teaching self-efficacy of pre-service teachers, whilst the Eysenck Personality Questionnaire (EPQ) was used to measure their personality dimensions. The findings revealed that pre-service teachers differed in terms of the extent of their teaching self-efficacy. The findings also revealed that gender and study programme had no influence on pre-service teachers’ teaching self-efficacy. The findings further revealed that there is no relationship between pre-service teachers’ teaching self-efficacy and personality factors, namely neuroticism (N) and extraversion (E). Furthermore, the findings revealed that the programme of study emerged as a significant predictor of efficacy in the classroom management subscale of teaching self-efficacy.